2009
DOI: 10.1126/science.1174229
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Deprivation Contributes to the Development of KRAS Pathway Mutations in Tumor Cells

Abstract: Tumor progression is driven by genetic mutations, but little is known about the environmental conditions that select for these mutations. Studying the transcriptomes of paired colorectal cancer cell lines that differed only in the mutational status of their KRAS or BRAF genes, we found that GLUT1, encoding glucose transporter-1, was one of three genes consistently upregulated in cells with KRAS or BRAF mutations. The mutant cells exhibited enhanced glucose uptake and glycolysis and survived in low glucose cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
708
5
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 827 publications
(750 citation statements)
references
References 39 publications
32
708
5
5
Order By: Relevance
“…This and the well-known property of glucose deprivation to promote mutations in TCs 20 prompted us to test whether clonal selection could account for changes in MCT1 and/or CD147 expression. It was ruled out by showing i) that the reintroduction of glucose after a starvation period of 24 h (resulting in increased MCT1 and CD147 protein expression) restored basal protein expression levels (Supplementary Figure 2B), and ii) that the glucose starvation of 2 independent clones isolated from the total SiHa population caused a significant increase in the expression of both proteins (Supplementary Figures 2C-D).…”
Section: Glucose Deprivation Stabilizes Mct1 and Cd147 Protein Expresmentioning
confidence: 99%
“…This and the well-known property of glucose deprivation to promote mutations in TCs 20 prompted us to test whether clonal selection could account for changes in MCT1 and/or CD147 expression. It was ruled out by showing i) that the reintroduction of glucose after a starvation period of 24 h (resulting in increased MCT1 and CD147 protein expression) restored basal protein expression levels (Supplementary Figure 2B), and ii) that the glucose starvation of 2 independent clones isolated from the total SiHa population caused a significant increase in the expression of both proteins (Supplementary Figures 2C-D).…”
Section: Glucose Deprivation Stabilizes Mct1 and Cd147 Protein Expresmentioning
confidence: 99%
“…SYNTHÈSE REVUES de la captation du glucose, de la glycolyse et de la production d'acide lactique, ainsi qu'un dysfonctionnement mitochondrial. De plus, le potentiel prolifératif des cellules transformées par K-Ras requiert une forte concentration en glucose et en glutamine dans le milieu de culture [15].…”
Section: Les Voies De Signalisation Impliquées Aktunclassified
“…26 However, it is not known whether mutant BRAF is sufficient to up-regulate GLUT1 expression. Therefore, we applied Western blot analysis to demonstrate that expression of GLUT1 significantly increased in cyst108 and RK3E cells expressing BRAF V600E as compared to those cells expressing BRAF WT 36 hours and 48 hours after transfection ( Figure 5, A and C).…”
Section: And B) As Shown Inmentioning
confidence: 99%
“…Furthermore, a recent study has demonstrated that BRAF expression is required for the expression of GLUT1, which encodes glucose transporter-1, and glucose deprivation is associated with the development of KRAS pathway mutations in tumor cells. 26 Thus, in this study, we also tried to determine whether mutant BRAF plays a causal role in up-regulating GLUT1 expression in our cellular model.…”
mentioning
confidence: 99%